Managing Covid-19 in an Era of Information Communication Technology: The Malaysia Experience - Zaini Othman; Mohd Mahadee Ismail; Eko Prayitno Joko (Human Resource Management Academic Research Society, 2021)
This article looks at the structural and non-structural management elements as applied by the Malaysia State in handling and managing the threat posed by unseen enemies, the Covid19 virus. This research utilizes non-participants' observations, and it argues that the joint and symbiosis efforts between state and society are vital in ensuring the state objectives to overcome the "attack" of the pandemic. The data shows that since the Covid-19 hit the nations, the matter has contributed to panic among many segments of society due to low socio-political literacy. This situation has created two opposite situational for the state to handle during the crisis. First, the crisis itself, and second, contain the virality of the false and unofficial news across society. Thus, this article concludes to deal with a crisis in a constructive manner, every country segment needs to be mutually symbiosis in their actions and behaviors, particularly their literacy level. The increasing use and exploration of information technologies have created a new way of human interaction, and above all has challenged and posed a new threat towards the concept of "privacy" and "security" within the larger context of integrity and socio-political stability of the Malaysian nation.